2022
DOI: 10.1002/pca.3105
|View full text |Cite
|
Sign up to set email alerts
|

Detailed investigation of the composition and transformations of phenolic compounds in fresh and fermented Vaccinium floribundum berry extracts by high‐resolution mass spectrometry and bioinformatics

Abstract: Introduction Blueberries are known for their very high content of biologically active phenolic compounds; nonetheless, differently from the North American and European species of blueberries, Neotropical blueberries have not been extensively studied yet. Objectives In the present paper, the phenolic composition of Vaccinium floribundum Kunth, which is endemic to the Andean regions and grows 1,600 to 4,500 meters above sea level, was investigated by ultra‐high‐performance liquid chromatography coupled to high‐r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 44 publications
7
8
0
2
Order By: Relevance
“…The total phenolic content was determined by the Folin-Ciocalteu reagent method obtaining a similar polyphenols concentration in fermented and non-fermented Pushgay berries (P: 2.38 ± 0.01 and FP: 2.95 ± 0.14 µg GAE/µg lyophilized berry) (Table 1), in line with previous data [32].…”
Section: Content Of Polyphenols In Berries Solutionssupporting
confidence: 85%
See 4 more Smart Citations
“…The total phenolic content was determined by the Folin-Ciocalteu reagent method obtaining a similar polyphenols concentration in fermented and non-fermented Pushgay berries (P: 2.38 ± 0.01 and FP: 2.95 ± 0.14 µg GAE/µg lyophilized berry) (Table 1), in line with previous data [32].…”
Section: Content Of Polyphenols In Berries Solutionssupporting
confidence: 85%
“…Cerrato et al [32] showed that glyco-conjugations were mostly hydrolyzed following fermentation, and a higher concentration of free flavonols was found, mainly quercetin (97% of the total flavonol content) [32]. In the untargeted analysis, Cerrato et al also identified, for the first time, a large number of phenolic acids and their derivatives (≈145 compounds) in FP and P; furthermore, anthocyanins in P were almost completely degraded after fermentation in phenolic acids [32]. In this study, we performed a targeted/quantitative analysis of quercetin (both the aglycone and glycoconjugate forms) through HPLC-ESI MS/MS (Table 1).…”
Section: Content Of Polyphenols In Berries Solutionsmentioning
confidence: 99%
See 3 more Smart Citations